2017
DOI: 10.1080/15548627.2017.1328347
|View full text |Cite
|
Sign up to set email alerts
|

Activation of DRD5 (dopamine receptor D5) inhibits tumor growth by autophagic cell death

Abstract: Dopamine agonists such as bromocriptine and cabergoline have been successfully used in the treatment of pituitary prolactinomas and other neuroendocrine tumors. However, their therapeutic mechanisms are not fully understood. In this study we demonstrated that DRD5 (dopamine receptor D5) agonists were potent inhibitors of pituitary tumor growth. We further found that DRD5 activation increased production of reactive oxygen species (ROS), inhibited the MTOR pathway, induced macroautophagy/autophagy, and led to au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 58 publications
3
74
0
1
Order By: Relevance
“…Furthermore, the mechanism for mTOR activation and induction of ACD was not restricted in pituitary tumour cells. Similar results were obtained with other human cancer cells, such as colon cancer, gastric cancer, and glioblastoma cells, due to the high expression of DRD5, suggesting a potential broad therapeutic application of CAB in different human tumours [5].…”
Section: Activation Of the Mammalian Target Of Rapamycin Pathway And supporting
confidence: 83%
See 3 more Smart Citations
“…Furthermore, the mechanism for mTOR activation and induction of ACD was not restricted in pituitary tumour cells. Similar results were obtained with other human cancer cells, such as colon cancer, gastric cancer, and glioblastoma cells, due to the high expression of DRD5, suggesting a potential broad therapeutic application of CAB in different human tumours [5].…”
Section: Activation Of the Mammalian Target Of Rapamycin Pathway And supporting
confidence: 83%
“…In addition, D2S was observed to activate phospholipase D, which may be linked to its potent antiproliferative effect [23]. Subsequent studies have revealed multiple mechanisms for the anti-proliferative function of dopamine agonists (DAs) [5,24].…”
Section: Suppression Of Cell Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been recognized that control of autophagy progression in cancer cells is an effective strategy to halt tumor growth [24, 25], as the molecular analyses of human cancers have revealed that autophagy regulators are frequently deregulated in most of the common malignancies [26, 27]. For this reason, autophagy inhibition has been regarded as a promising anticancer strategy to inhibit the multiple cellular processes.…”
Section: Discussionmentioning
confidence: 99%